Deuterium target polarimeter at the vepp-3 storage ring; Polarized sources and targets - Dyug M. V.; Lazarenko B. A.; Mishnev S. I.; Nikolenko D. M.; Rachek I. A.; Shestakov Y.V.; Sadykov R. S.; Toporkov D. K.; Zevakov S. A.; Osipov A.V.; Stibunov V. N. Victor Nikolaevich (2003, 2003)
В фонде НТБ ТПУ отсутствует